2012
DOI: 10.3174/ajnr.a3060
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Frontal Lobe Gray Matter Perfusion in Cognitively Impaired Patients with Secondary-Progressive Multiple Sclerosis Detected by the Bookend Technique

Abstract: BACKGROUND AND PURPOSE:There is increasing evidence implicating microvascular impairment in MS pathogenesis. Perfusion imaging offers a unique opportunity to investigate the functional impact of GM pathology. We sought to quantify differences in MR imaging-based bookend-derived cerebral perfusion between cognitively impaired and nonimpaired patients with SPMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
5
35
0
Order By: Relevance
“…20 The second study interrogated both cortical and subcortical GM at the region-of-interest level. 21 Our study represents the extension of that work to the voxel level and the inclusion of a multivariate analytic approach that incorporated data from multiple discrete cognitive domains. We hypothesized that cognitively impaired patients with SPMS exhibit decreased cerebral perfusion in functionally relevant brain regions, such as the prefrontal cortex, compared with nonimpaired patients with SPMS, and that these reductions would remain significant in the context of global GM, WM, and WML volumes.…”
Section: -8mentioning
confidence: 99%
See 2 more Smart Citations
“…20 The second study interrogated both cortical and subcortical GM at the region-of-interest level. 21 Our study represents the extension of that work to the voxel level and the inclusion of a multivariate analytic approach that incorporated data from multiple discrete cognitive domains. We hypothesized that cognitively impaired patients with SPMS exhibit decreased cerebral perfusion in functionally relevant brain regions, such as the prefrontal cortex, compared with nonimpaired patients with SPMS, and that these reductions would remain significant in the context of global GM, WM, and WML volumes.…”
Section: -8mentioning
confidence: 99%
“…The bookend technique is a novel DSC calibration methodology that more accurately quantifies cerebral perfusion by using pre-and postgadolinium "bookend" scans. [17][18][19] Only 2 prior cerebral perfusion studies have explicitly investigated cognitive impairment in MS. 20,21 Using a quantitative DSC technique, the first study reported significant correlations between subcortical GM CBF and the Rey Complex Figure Test score and subcortical GM CBV and the Delis-Kaplan Executive Function System score, though cortical tissue was not assessed. 20 The second study interrogated both cortical and subcortical GM at the region-of-interest level.…”
Section: -8mentioning
confidence: 99%
See 1 more Smart Citation
“…This quantitation process was performed automatically and without manual intervention by using in-house software written in Matlab (Matlab 2009a; Mathworks, Natick, Mass), based on the bookend method outlined above and previously applied in clinical studies of cancer (18,19), multiple sclerosis (20), and acute stroke (21). In large clinical studies this automated perfusion quantitation technique has been found to be robust, repeatable, and reliable (15).…”
Section: Pet Protocolmentioning
confidence: 99%
“…11,14 Given the recent emphasis on the role of GM pathology both in the etiology of MS and related cognitive dysfunction, FA was considered in the context of GM volume using multivariate regression. [15][16][17] Normal-appearing white matter has also been investigated using magnetization transfer ratio. 18 Tract-based spatial statistics (TBSS) is being increasingly utilized in DTI studies of MS and cognition.…”
mentioning
confidence: 99%